Legislative regulation of foreign investment in China during the period of reforms and openness - Лизогуб, Віталій Анатолійович (Theory and practice of jurisprudence, 2017)
The article is devoted the complex analysis of the reform process in China in the late twentieth century, in particular, main directions, purposes, tasks, peculiarities of the policy of modernization and openness. Examines the main aspects of «socialism with Chinese characteristics», the state, strategies and objectives of the legislation on foreign investments are considered, methods, nature and peculiarities of its development are determined. Thanks to the detailed study of a significant number of monographic literatures established methods, character, and peculiarities of transformations in the People's Republic of China. Foreign investment has a number of advantages over other forms of economic development. In particular, they provide an additional source of capital investments in the production of goods and services, in some cases in the form of the transfer of advanced technologies, know-how, advanced management methods. In addition, they do not pose a heavy burden on the state budget, do not affect the external debt of the state. The inflow of foreign investment can be considered one of the indicators of openness of the economy and its high competitiveness. In China it is believed that the consumption of investment and exports is a "triple", which brings the Chinese economy to the new frontiers. The regulatory framework for foreign investment in China consists of the following basic legislative acts: laws "On Joint Ventures with Chinese and Foreign Capital", "On Companies with Foreign Capital", etc., as well as a significant number of sub-legislative normative documents (instructions, instructions etc). The problematic aspects in the field of investment are: the complexity of tax collection, the lack of a regulated dispute resolution system, and most importantly, the lack of investor protection, primarily the lack of protection of intellectual property rights. As a result of reforms and the implementation of the openness policy, China has achieved tremendous success in the field of investment regulation, as well as radically reformed the legislative framework in the field of investment activity. China continues to be the leader in terms of economic growth.